2016
DOI: 10.1124/mol.116.106617
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Berberine Modulates Hepatic Lipid Metabolism by Altering Microbial Bile Acid Metabolism and the Intestinal FXR Signaling Pathway

Abstract: Previous studies suggest that the lipid-lowering effect of berberine (BBR) involves actions on the low-density lipoprotein receptor and the AMP-activated protein kinase signaling pathways. However, the implication of these mechanisms is unclear because of the low bioavailability of BBR. Because the main action site of BBR is the gut and intestinal farnesoid X receptor (FXR) plays a pivotal role in the regulation of lipid metabolism, we hypothesized that the effects of BBR on intestinal FXR signaling pathway mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 65 publications
8
106
1
2
Order By: Relevance
“…1C). Previous studies indicated that 2 or 8 weeks of BBR treatment affected bile acid biosynthesis (Guo et al, 2016;Sun et al, 2017). Analysis of bile acid composition showed that 5 days of BBR treatment significantly increased taurine-conjugated bile acid levels in the feces, liver, and ileum (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…1C). Previous studies indicated that 2 or 8 weeks of BBR treatment affected bile acid biosynthesis (Guo et al, 2016;Sun et al, 2017). Analysis of bile acid composition showed that 5 days of BBR treatment significantly increased taurine-conjugated bile acid levels in the feces, liver, and ileum (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Since BBR has low bioavailability, modulation of gut bacteria might be one possible mechanism for its antidiabetic and antiobesity effects (Han et al, 2011;Xie et al, 2011). Recent evidence suggested that the lipidlowering effect of BBR involves modulation of bile acid composition and activation of intestinal FXR signaling (Guo et al, 2016;Sun et al, 2017). However, the underlying mechanisms by which BBR modulates the intestinal bacteria community leading to microbially induced signals have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that oral berberine is poorly absorbed and exhibits an extremely low plasma exposure and a high gut accumulation (24)(25)(26)(27)(28)(29). To determine whether berberine exerted a local action in the gut under arthritis status, we compared the pharmacokinetics and tissue distribution of berberine in normal and CIA rats after 14 d of oral administration at a dose of 200 mg/kg.…”
Section: Berberine Exerted Antiarthritis Effect Through Modulation Ofmentioning
confidence: 99%
“…The evidence indicated that orally administered berberine showed an extremely low bioavailability (<1%) and a dominant gut accumulation (24) and that the positive charge on the nitrogen atom in the berberine molecule promotes its binding to bacteria where it exerts an antibacterial effect. Recent studies indicated that berberine lowered hyperlipidemia and modulated bile acid metabolism by altering the gut microbiota and the SCFA production (2529). Moreover, our recently published data showed that berberine exerted an antiarthritic effect in a gut‐dependent manner (30).…”
mentioning
confidence: 99%
“…TMC is a potent FXR antagonist and its accumulation decreases FXR signaling in the intestine (55)(56)(57). Intestinal FXR knockout animals have been shown to be resistant to diet-induced obesity, insulin resistance, and NAFLD (58)(59)(60). It has also been shown that loss of intestinal FXR activity leads to induced GLP-1 (glucagon-like peptide 1) production, which leads to improved glucose metabolism (61).…”
Section: Arv1mentioning
confidence: 99%